Risk factors for neurological complications in adult ECMO patients: a systematic review and meta-analysis - Dong, Meijun; Gu, Peipei; Cai, Lingyun; Zhu, Yan; Sheng, Li; Liang, Jiangshuyuan; Zhao, Shuhua; Zeng, Fei (Frontiers in Medicine, 2026)
ObjectiveAiming to systematically review risk factors for neurological complications in adults receiving ECMO support.MethodsA comprehensive computerized search was conducted in Chinese and English databases for studies examining risk factors of neurological complications in adult ECMO patients, supplemented by manual and reference tracking, with the search period extending up to April 2025. Meta-analysis and sensitivity analyses were performed using Stata 18.0 software. 29 studies involving 62,656 patients were included. The meta-analysis results showed that female sex, pre-ECMO cardiac arrest, renal replacement therapy, and cardiac insufficiency were influencing factors of composite neurological complications in adult ECMO patients. Female sex and ECMO duration were risk factors of stroke. Female sex, pre-ECMO lactate, pre-ECMO pH, platelet count, low platelets, APTT, and vasoactive drug use were risk factors of intracranial hemorrhage. The pooled results for female sex in the stroke group was not robust. Significant publication bias was observed for composite neurological complications outcomes, whereas no significant publication bias was detected for stroke or intracranial hemorrhage.ConclusionGiven the diverse etiologies underlying neurological injury in adult ECMO recipients, protocolized neurological monitoring and prompt intervention for detected abnormalities are strongly recommended.Systematic review registrationPROSPERO (CRD420251069285).